KAJIAN HUKUM KESEPAKATAN PARA PIHAK DALAM MENCAPAI PENETAPAN PUTUSAN VERSTEK PERKARA PERCERAIAN (Riset Studi Kantor Hukum Arif Sasongko SH & Partners) - Irwan Irwan; Ichwan Setiawan (Universitas Muhammadiyah Ponorogo, 2023)
In divorce cases in court, the defendants and plaintiffs cannot always attend court proceedings in accordance with legal determinations. Absence on the appointed day can cause the divorce to be decided by way of verstek by the judge. This research intends to identify and explain how agreements outside the court are formed before a petition or application is submitted from one of the parties (the plaintiff or the plaintiff) to obtain a collective agreement to reach a verstek decision in divorce matters. The research method used is empirical law research with a qualitative research type. The result of the discussion is that a mutual agreement before the divorce trial is needed to facilitate the implementation of the divorce trial. With the existence of a mutual agreement, the divorce trial can be carried out in the absence of the applicant and the respondent which is finally decided by way of verstek by the court judge. It is hoped that all parties related to the enforcement of divorce issues should fight for peace before the implementation of the divorce trial so that they can reduce divorce cases which are increasing day by day.